Comparison of the Functional OutcomeBetween Intra-Articular Corticosteroid Injection versus Platelet-Rich Plasma in Patients with Adhesive Capsulitis - Ijaz Ahmad; Noreen Akhtar; Aamir Waheed Butt; Abdul Latif Khattak; Hina Kanwal Shafaat; Farah Mahboob (Pakistan Armed Forces Medical Journal, 2023)
Objective: To compare mean resting pain relief and passive external rotation improvement by Intra-articular Steroid versus intra-articular Platelet Rich Plasma injection in patients with adhesive capsulitis.